Achievements and an outlook of 2012-2021 research: Instituto de Investigaciones en Ciencias Biomédicas of Universidad Ricardo Palma: Logros y perspectivas de la investigación 2012-2021: Instituto de Investigaciones en Ciencias Biomédicas de la Universidad Ricardo Palma - De La Cruz-Vargas, Jhony A. (2022)
Write about achievements and and outlook of research in the last ten years from the Instituto de Investigaciones en Ciencias Biomédicas (INICIB) of Universidad Ricardo Palma, it is relevant because research currently occupies a central place in universities, at least rethorically.We present an overview of the evolution of scientific publication, which constitute a real and objective indicator to visualize the trends and projections of research at the Faculty of Human Medicine and at Universidad Ricardo Palma. For this, we will take as reference the records of international bases of recognized prestige as SCOPUS and WEB OF SCIENCE.